Manual material handling analysis using biomechanics at repair department workers - Chandra, Huki (LPPMPK - Sekolah Tinggi Teknologi Muhammadiyah Cileungsi, 2023)
The use of manual labor in production process activities in a company is still required, especially in the process of moving materials or products to the next workstation. This activity is often referred to as Manual Material Handling (MMH). Lifting weights that are not according to standards and MMH activities that are not properly carried out by workers have a risk of accidents and diseases such as low back pain. The analysis used in this study is using biomechanical calculations. Based on the load and lifting posture carried out by the worker, it resulted in 3,885 N of compression force, it can be concluded that the lifting level is included in the cautious category. Through the same calculation, it is obtained that the maximum load that may be lifted in the safe category is 11.28 kg. Lifting with two hands can reduce the load on Fc L5/S1 to 2,423 N, this can be done by changing the diameter of the two-handle bucket